Pojęcie interesu w perspektywie głównych ujęć teoretycznych stosunków międzynarodowych - Kabat-Rudnicka, Danuta (Polski Przegląd Stosunków Międzynarodowych, 2018)
The concept of interest in view of key theoretical approaches in international relations Conceptual category of interests, and especially of the national interest, belongs to a group of key terms in the dictionary of politics of each state. The concept of national interest occupies a central place in the theory of international political relations, constituting an important conceptual and practical point of reference. For some theories, such as traditional realism, it is a central concept around which further considerations are made, whereas for others, such as the one referring to Marxism, it serves as an instrument, a proverbial “smoke screen”, for creating a rationale and hiding real reasons for the decisions taken. The aim of this article is to present the concept of national interest through the prism of key theories of international relations, i.e. traditional approaches such as realism and liberalism, critical such as Marxism and progressive approaches such as the English school and constructivism.